Dendrite remelting during rapid solidification of undercooled CoSi-CoSi2 eutectic alloys quantified by in situ synchrotron X-ray diffraction. (15th March 2021) - Baker, Evan B.; Jeon, Sangho; Shuleshova, Olga; Kaban, Ivan; Wang, Yeqing; Gao, Jianrong; Kolbe, Matthias; SanSoucie, Michael P.; Matson, Douglas M.
Graphical abstract: Image, graphical abstract Abstract: The relationship between remelting and undercooling in Co38.2 Si61.8 (at. %) eutectic alloys is investigated with in situ X-ray diffraction experiments and microstructural observations. High-energy in situ X-ray diffraction during uncoupled eutectic solidification of undercooled Co38.2 Si61.8 allows the phase fractions to be tracked through time and reveals remelting of primary solid coincident with the formation of secondary solid. Microstructure analysis suggests that remelting occurs at the supersaturated dendrite interior. The remelted solid fraction is quantified for a wide range of solidification conditions and found to be strongly correlated with the secondary undercooling of the melt, yet independent of convection and containerless processing technique. A remelting limit was observed in experiments with primary CoSi2, indicating that system-specific factors impose additional constraints.